Human Rights And Policy At The Margins: Evaluating Serang City’s Regional Regulation No.2 Of 2010 In Addressing Lgbtq+ Realities - Yandika Aprillianto; Riswanda Riswanda (Jurnal Administrasi Publik, 2025)
Serang City Regional Regulation Number 2 of 2010 concerning Prevention, Eradication, and Management of Social Diseases explicitly prohibits homosexual and lesbian acts and prohibits transgender people from engaging in sex work. The prohibition is framed as an act that violates public order and health, this regional regulation also reflects the moral panic over LGBTQ+ issues in Indonesia when there is no national law for LGBTQ+ status on any basis. The gap between regional moral regulations and human rights principles, along with reports of a growing underground LGBTQ+ community and increasing HIV cases in Serang, demands a policy evaluation regarding the effectiveness and implications of Serang City Regional Regulation Number 2 of 2010, and reframing the issue from the perspective of public policy and human rights, no longer a moral issue or “social disease”. The evaluation is structured using Charles O. Jones’ framework that assesses the political, organizational, and substantive dimensions of policy performance and is enriched with insights from the policy literature. The results of the study show that evaluations based on the political and substantive dimensions show regulatory failure and have not been effective in achieving the objectives of handling the LGBTQ+. Meanwhile, evaluations based on the organizational dimension are viewed positively. The LGBTQ+ receives more attention when viewed from a health perspective compared to morals and social contexts in Serang City. Evaluation notes require policy attention based on values and human rights because these two things are not the basis for the presence of this policy.